Private Practice, Public Gratitude: Following the Traces of Information Behaviours in Acknowledgement Paratext - Desrochers, Nadine; Pecoskie, Jen (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Using qualitative content analysis of award-nominated works, this research focuses on information practices documented within acknowledgement paratext in published codices. These paratextual records illustrate the permeability of the local and global contexts in writing and publishing practices. Interactions with information sources reveal gaps information professionals may be able to address. À l’aide d’une analyse de contenu qualitative d’œuvres primées, cette recherche porte sur les pratiques informationnelles documentées dans les entrées paratextuelles de remerciement de codex publiés. Ces entrées paratextuelles illustrent la perméabilité des contextes locaux et mondiaux dans les pratiques de rédaction et de publication. Les interactions avec les sources d’information révèlent des écarts que les professionnels de l’information pourraient être en mesure d’étudier. ***Best Overall Paper Award Winner***